The role of green accounting environmental on reducing pollution resulting from the telecommunications sector in Sudan (Sudani company case study) - Ahmed, Rogia Eltayb Ali (Journal of Economic, Administrative and Legal Sciences, 2021)
The study aimed to know the role of green accounting in the telecommunications sector in Sudan and to show its impact in reducing the environmental harms resulting from its activity by applying to a Sudanese company in testing two hypotheses. The first is that there is a positive relationship between the application of green accounting and the radioactive pollution of communication towers. And the second hypothesis is a positive relationship between the application of accounting. Green and increasing environmental awareness, the study used the inductive approach and the descriptive analytical approach, where the inductive approach was used through the role of green accounting in environmental pollution in communications in Sudan from a Sudanese company as a case study with the use of the descriptive analytical approach through metadata collected from a questionnaire distributed on a random sample of 40 employees of the company and their results analyzed. The most important results concluded that green accounting leads to a reduction in environmental pollution by inference to the percentage of those who agree to that 79% of the respondents and that the companies ’commitment to applying green accounting leads to an increase in environmental awareness by inference that the percentage of those who agree to that is 73% of the respondents, and the study recommended many The recommendations, most notably the necessity to oblige companies to apply green accounting, raise the level of environmental awareness and disclose this in their reports.
Keywords: Social responsibility; Telecommunications towers; Environmental awareness